2018
DOI: 10.15540/nr.5.4.109
|View full text |Cite
|
Sign up to set email alerts
|

Using Neurofeedback to Improve ADHD Symptoms in School-Aged Children

Abstract: The diagnosis and treatment of the behaviors associated with attention-deficit/hyperactivity disorder (ADHD) predominantly involves pharmacological interventions. Many children experience significant negative side effects (e.g., appetite suppression, insomnia, headaches, stomachaches, irritability, and impaired height) from the initial and continued use of stimulant medication. Consequently, many parents are motivated to consider alternative treatments for ADHD such as neurofeedback. This paper presents an arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Further studies indicated that modulating brain activity provided long-term neural-network stability and neuroprotection against various toxins and neurodegeneration (da Silva-Sauer et al, 2019). Neurofeedback therapy has gained recognition as an appropriate intervention for conditions ranging from PTSD, ADHD, learning disabilities, and emotional dysregulation (Hammond, 2011;McReynolds, Bell, & Lincourt, 2017;McReynolds, Britt & Villalpando, 2019;McReynolds, Villalpando & Britt, 2018).…”
Section: Neurofeedback Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies indicated that modulating brain activity provided long-term neural-network stability and neuroprotection against various toxins and neurodegeneration (da Silva-Sauer et al, 2019). Neurofeedback therapy has gained recognition as an appropriate intervention for conditions ranging from PTSD, ADHD, learning disabilities, and emotional dysregulation (Hammond, 2011;McReynolds, Bell, & Lincourt, 2017;McReynolds, Britt & Villalpando, 2019;McReynolds, Villalpando & Britt, 2018).…”
Section: Neurofeedback Therapymentioning
confidence: 99%
“…Auditory processing difficulty (APD) does not pertain to hearing loss as measured in standard audiological screenings; rather, it is the manner in which the brain processes auditory stimuli (McReynolds et al, 2018;McReynolds et al, 2019). APD can be identified at any age.…”
Section: Auditory Processing Difficultiesmentioning
confidence: 99%
See 3 more Smart Citations